STUDY OF ROLLING DIRECTION OF TIN AND ITS EFFECT ON ADHESION PHENOLIC EPOXY RESINS - Reátegui S., Scila (2007)
The existing relation between the adhesion of epoxilenolic resin and the sense of lamination of the tin plate by means of gravimetric, microscopic and electromechanical tests studies in a random sample that evaluates the resistance to the abrasion, the percentage of porosity and rugosity. The resin deposited in cross-sectional form presents up to 43,7% of diminution of mass given off by abrasion, with respect to the deposited one following the sense of lamination of the tin plate. lt has been observed that exists a proportional relation between the percentage of adhesion and the porosity produced by the effect «crosspiece». Also, the framework that the polymeric form with the substrate, in a cross-secional application, produces a high resistance to the electric flux that reduces the current passage up to 50.6%.